MOTIVATION, DISCIPLINE, AND EMPLOYEE PERFORMANCE IN THE SOUTH TANGERANG FIRE AND RESCUE SERVICE - Priska Widya Anggraeni (Jurnal Ilmiah Manajemen dan Bisnis, 2026)
This study aims to analyze the effect of motivation and work discipline on employee performance at the South Tangerang City Fire Department. The validity and reliability tests indicated that all indicators of motivation (X1), work discipline (X2), and performance (Y) were valid and reliable. The partial test (t-test) showed that motivation (tcount = 2.887; sig. 0.008) and work discipline (tcount = 2.160; sig. 0.000) have a positive and significant effect on performance. The coefficient of determination revealed that motivation explains 58.2% of performance variation, while work discipline explains 53.4%. Simultaneously, the F-test (Fcount = 24.374; sig. 0.000) confirmed that motivation and work discipline together significantly influence performance, with a contribution of 64.4%. Therefore, motivation and work discipline are proven to have a positive, strong, and significant effecton employee performance.